CLOVES syndrome caused by mosaic mutation in the PIK3CA gene identified in fibroblasts - Kłaniewska, Magdalena; Rydzanicz, Malgorzata; Kosińska, Joanna; Biela, Mateusz; Walczak, Anna; Szmida, Elżbieta; Rozensztrauch, Anna; Płoski, Rafał; Śmigiel, Robert (Pediatria Polska - Polish Journal of Paediatrics, 2021)
CLOVES syndrome is a rare dysmorphic syndrome with multiple defects caused by somatic activating mutations in the PIK3CA gene on chromosome 3q26.32. There are currently less than 200 individuals worldwide living with CLOVES syndrome (OMIM: 612918, ORPHA: 140944). Due to the extremely low prevalence rate of CLOVES syndrome, few epidemiological data are available in the literature. We report 4-year-old girl with somatic mutation in the PIK3CA gene (c.1357G> A) in fibroblast, revealed in the WES study, confirming the diagnosis of CLOVES syndrome. CLOVES syndrome can be very difficult to diagnose, not only because of its extreme rarity, but also due to symptoms which vary both in range of symptoms and severity. Therefore, the case described by us may be helpful in the correct diagnosis of this rare disease in subsequent cases and makes an important contribution in rare disease diagnostics.